Evaluation of the i-gel® Plus supraglottic airway device in elective surgery: a prospective international multicentre study - Werner, Jakub; Klementova, Olga; Bruthans, Jan; Macoun, Jaromir; Gaszynski, Tomasz; Henlin, Tomas; Donaldson, Will; Lichnovsky, Erik; Arava, Shiva; Lopez, Ana M; Berge, Raquel; Michalek, Pavel (Anaesthesia, 2024)
BACKGROUND: The i-gel® Plus is a modified version of the i-gel® supraglottic airway device. It contains a wider drainage port; a longer tip; ramps inside the breathing channel; and an additional port for oxygen delivery. There has been no prospective evaluation of this device in clinical practice. METHODS: This international, multicentre, prospective cohort study aimed to evaluate the performance of the i-gel Plus in adult patients undergoing elective procedures under general anaesthesia. The primary outcome was overall insertion success rate, defined as the ability to provide effective airway management through the device from insertion until the end of the surgical procedure. Secondary outcomes included device performance and incidence of postoperative adverse events. Data from the first 1000 patients are reported. RESULTS: In total, 1012 patients were enrolled; 12 forms were excluded from the final analysis due to incomplete data leaving 1000 included patients (545 female). Overall insertion success rate was 98.6%, with a first-attempt success rate of insertion of 88.2%. A significant difference between females and males was seen for the overall success rate (97.4% vs. 99.6% respectively) but not for first-attempt successful insertion. Mean (SD) oropharyngeal seal pressure was 32 (7) cmH2O. The only independent factor that increased the risk of first-attempt failure was low operator experience. Complications included desaturation < 85% in 0.6%; traces of blood on the device in 7.4%; laryngospasm in 0.5%; and gastric contents inside the bowl in 0.2% of patients. CONCLUSIONS: The i-gel Plus appears to be an effective supraglottic airway device that is associated with a high insertion success rate and a reasonably low incidence of complications.
Keywords: celková anestezie; prospektivní studie; Airway Management; intratracheální intubace; Humans; lidé; Equipment Design; lidé středního věku; Anesthesia, General; elektivní chirurgické výkony; laryngální masky; Middle Aged; design vybavení; Female; Male; Prospective Studies; Adult; Elective Surgical Procedures; mužské pohlaví; Cohort Studies; Aged; ženské pohlaví; Postoperative Complications; dospělí; kohortové studie; pooperační komplikace; Intubation, Intratracheal; Laryngeal Masks; zajištění dýchacích cest; senioři